Increased content and uniformity of enzyme-induced calcite precipitation realized by prehydrolysis and an accelerated injection rate - Zhu, Chenhao; Li, Zhiqing; Zhang, Zhongjian; Zhang, Yu; Zhou, Yingxin; Wang, Jianhong (Frontiers in Earth Science, 2023)
The utilization of enzyme-induced calcium carbonate precipitation (EICP) to consolidate aeolian sand has received significant attention in recent years. When EICP was used and cementing solution was injected in stages, the calcium carbonate content and uniformity were not improved simultaneously. A method is proposed to alleviate this problem by pre-reacting urea and urease before injecting the cementing solution and speeding up the injection rate. Experiments were designed to compare staged injections of EICP-cemented aeolian sand with and without the use of prehydrolysis and with different injection rates. The results show that (1) at the same injection rate, the content of calcium carbonate in the prehydrolysis samples after 12 injections was 66.1% higher than that in the samples without prehydrolysis. (2) When using prehydrolysis, the calcium carbonate content as a function of the injection rate decreased in the following order: 10 ml/min > 15 ml/min > 7.5 ml/min. The highest amount of calcium carbonate was generated at an injection rate of 10 ml/min and was mainly distributed on the surface. The calcium carbonate generated with an injection rate of 15 ml/min was uniformly distributed in the sand. These results indicate that the method could improve the efficiency of calcium carbonate generation and distribution uniformity, and could also be applied to form a hard crust on the surface of sandy soil or for reinforcing sandy soil by multiple injections.